BUDAYA LOKAL VERSUS ISLAM: PERSETERUAN ANTARA BUPATI PURWAKARTA DAN FPI DALAM KERANGKA DEMOKRATISASI DAN DESENTRALISASI - Yanwar Pribadi (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2016)
This paper explores the relationship between Islam and local culture in Indonesia in the framework of democratization and decentralization. It specifically focuses on the dispute between Islamic Defenders Front’s (the FPI) leader, Habib Rizieq and the Regent of Purwakarta, Dedi Mulyadi together with the West Java Siliwangi Youth Wing (AMS). This paper shows that local leaders in decentralizing and democratizing Indonesia have involved in the turbulent political arenas, and this process in turn helps shape the contours of the country’s political situation. This paper also shows that the on-going processes of decentralization and democratization have allowed for the emergence of new seemingly-autonomous local leaders, such as Dedi Mulyadi and Habib Rizieq. This paper argues that the rise of more overt expressions of Islamic piety and cultural resilience has shaped and characterized the identity politics of certain influential people’s leaders.